Pengaruh Biochar terhadap Pertumbuhan Padi dalam Sistem Aerobik - Suli Suswana (Agrotechnology Research Journal, 2019)
An application of biochar to the intensive weathered soils potentially can change physical and chemical properties of the soils, improved soil function and increased yield of crops. A meta-analyses evaluation showed a significant correlation between biochar and plants productivity,  that means there are benefits of biochar application to the soils on plants productivities, that was increased 10%.This experiment was used Randomized Completed Block Design with 8 treatments and 3 replications. The treatments are: contr), 20 ton biochar ha-1, 40 ton biochar ha-1, 50 ton biochar ha-1, 60 ton biochar ha-1, 10 ton biochar + 10 ton poultry litter ha-1, 20 ton biochar + 20 ton poultry litter ha-1, 30 ton biochar + 30 ton poultry litter ha-1.  The results showed biochar 20 ton ha-1 could increase significantly of plant heigh, number of punicles per clump, and the weight dried straw per clump. Whereas, application combination 20-30 ton biochar ha-1 + 20-30 ton poultry litter ha-1 could increase amount of tillers per clump, amound of punicles per clump, and weight dried straw (total biomass) per clump significantly.